The concept and essence of legal communication in a modern information space - Макеєва, Олена Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
The article deals with the concept and role of legal communication in a modern information space. It is proved that legal communication is a set of processes and entities that provide purposeful circulation and dissemination of normative legal information and legal knowledge in the conditions of formation of the information society. The conclusion that the legal culture of subjects of legal communication is a prerequisite for the formation of an information and legal society in Ukraine is made.